1982
DOI: 10.1128/jvi.41.1.30-41.1982
|View full text |Cite
|
Sign up to set email alerts
|

Genomic RNA of mengovirus V. Recognition of common features by ribosomes and eucaryotic initiation factor 2

Abstract: Binding of ribosomes to the 32P-labeled genomic RNA of mengovirus was studied in lysates of mouse L929 and Krebs ascites cells under conditions for initiation of translation. Upon total digestion with RNase Tl, the 32P-labeled RNA protected in either 40S or 80S initiation complexes yielded four unique, large oligonucleotides. Each of these oligonucleotides occurred once in the viral RNA molecule. The same four oligonucleotides were recovered from 80S initiation complexes formed in lysates in which unlabeled me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Indeed, it has been shown (1, 14, 23, 32) that on a molar basis, mengovirus mRNA competes 35 times more effectively in translation than does globin mRNA; that is, half-maximal inhibition of globin synthesis occurred in lysates that contained 35 molecules of globin mRNA for every molecule of mengovirus RNA. Also, mengovirus mRNA binds eIF-2 with a 30-fold-higher affinity than globin mRNA (29,32). These observations suggest that under limiting conditions of protein synthesis, mengovirus mRNA may still be translated to a sufficient degree for progeny virus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown (1, 14, 23, 32) that on a molar basis, mengovirus mRNA competes 35 times more effectively in translation than does globin mRNA; that is, half-maximal inhibition of globin synthesis occurred in lysates that contained 35 molecules of globin mRNA for every molecule of mengovirus RNA. Also, mengovirus mRNA binds eIF-2 with a 30-fold-higher affinity than globin mRNA (29,32). These observations suggest that under limiting conditions of protein synthesis, mengovirus mRNA may still be translated to a sufficient degree for progeny virus formation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the fingerprints obtained upon terminal RNase T1 digestion of the fragments associated with either the 80S or the 40S initiation complexes in lysates of control or IFNtreated cells were just undistinguishable. The complexity of the pattern observed and the previous location of these oligonucleotides in two clusters of the RNA molecule (17) suggested that the in vitro translation of picornavirus RNA involved a novel mechanism of initiation.…”
mentioning
confidence: 95%
“…These results, however, left unanswered the major issue regarding the ability of ribosomes of IFN-treated cells to recognize and interact with the proper areas of the mRNA. Accordingly, the fragments of 32P-labeled mengovirus RNA selected for by ribosomes of IFN-treated cells at initiation of translation were isolated and fingerprinted by procedures fully described elsewhere (17). Four large T1-resistant oligonucleotides were obtained upon terminal digestion with RNase T1 of the fragments of mengovirus RNA protected in the 80S initiation complexes formed in lysates of untreated L-cells (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations